A escola e as mulheres em privação de liberdade: o cotidiano de uma turma de alfabetização entre a cela e a sala de aula. - Maria Cristina da Silva (2016)
This thesis aims to present the acquisition of reading and writing processes of women deprivation of liberty of a school in a prison unit in the state of Minas Gerais. The study that took as methodological principle to ethnographic research, recorded in a diary notes about the students in a class literacy and the various activities carried out by the teacher, as well as group activities provided by all school personnel, by an eight months. We attempted to these field reports capture the role of reading and writing at the school context, how it develops reading and writing on it, the meanings that the school and school activities are for research subjects. The research points to the presence of various genres and various carriers texts in the prison world where the restrictions do not apply to texts, but the conventions and rules of discipline and control: Control of incarcerated women and professionals who work in school. The restriction is most evident in the imposition of rules established by the prison on the school routine producing tensions and disputes. The school appears as required by the rule of law and is endorsed by the prison as important for redemption penalty and social rehabilitation of inmates. For them, the classroom goes beyond learning to read and write, it is a space outside the cell, living with others who are not in jail, listening to personal issues, counseling. The search for decreasing the time spent in prison, to exchange information. Freer conversations, laugh, cry, play. The school aims to provide education taking it as a human right. The working conditions are precarious and temporary employment relationship. Teachers have no qualifications to work in adult education in prisons, nor receive support from the State Department of Education for both.